PENGARUH TEKNIK AKUPRESUR TERHADAP LAMANYA PERSALINAN KALA I DI UPT PUSKESMAS TANJUNG BALAI - Dian Issabella, Betharia; Aidina, Dyka; Jannah, Miftahul (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2025)
Labor is a physiological thing experienced by everyone, but this physiological condition can become pathological if a mother does not know the physiological conditions and a helper or health worker does not understand how a labor is said to be physiological and how to manage it so that it can help reduce maternal mortality. Long labor is caused by inadequate uterine contractions (his) so that the opening of the cervix is slow which results in the mother experiencing fatigue and exhaustion. Inadequate uterine contractions can cause intrapartum and postpartum bleeding. Acupressure produces the hormone oxytocin, which can accelerate the opening of the first stage of labor and affect the progress of labor. One of the acupressure points that can be applied to accelerate the progress of labor is at point LI4. This study aims to determine the effect of acupressure technique on the duration of labor in the first stage. The research method is quasy experiment. The design of the quasy experiment design used was Two group post test Only Design. This research was conducted in the work area of the Tanjung Balai Karimun Health Center, the sample in this study were 80 women in labor during the active phase I. The results of the study in the control group were 8.5 times. The results of the study in the control group were 8.45 hours, with a range of 5-12 hours, in the Acupressure Group it was shorter, namely 6.23 hours, with a range of 4-9 hours with p = 0.000 (p < 0.05) it can be concluded that there is an effect of acupressure technique on the length of labor phase I at UPT Puskesmas Tanjung Balai Karimun Regency in 2024. It is recommended to be able to implement acupressure action as an alternative to accelerate the length of labor in Stage I.